Relation between Start Reaction Time and Performance Time among Women Finalist Sprinters in the Olympic Games 2000 to 2020 - Bandyopadhyay Nita; Ankur Ankur (OVS LLC, 2023)
Background. Success in sprinting events broadly depends on many factors. Among them, the reaction time at starting is one of the main factors that help sprinters get success by increasing their confidence and helping to avoid false starts. Study purpose. The purpose of the study was to find out the relationship between reaction time and performance time among women finalist sprinters in six Olympic Games since 2000. Materials and methods. Data were collected from 227 (n = 227) women finalist sprinters in the event of 100m (n= 47), 200m (46), 400m (43), 100m H (45), and 400m H (46) in 6 Olympic Games from 2000 to 2020, based on published official reports on worldathletics.org and olympedia.org websites. Data were considered from 227 samples from a total of 240 finalist women, where 13 were excluded because of a false start, being disqualified for doping, or failing to finish. Descriptive statistics, the Pearson correlation coefficient and simple regression analysis were used to determine the relationship between reaction time and performance time of the finalist women sprinters. The significance level was set at 0.05. Further Gaval'a 5-point scale was used to categorize the women sprinters based on their reaction times in five sprint events. Results. The results showed that there was a low positive correlation between reaction time and performance time among the sprinters in the 100m (r = 0.369, p<0.05) and 100m H (r = 0.367, p<0.05) events, whereas no relation was confirmed in 200m, 400m and 400m hurdles among women sprinters who participated in 2000-2020 Olympics. The 5-point scale revealed that 33.48% of sprinters belong to the average category, while 25.99% are in the unsatisfactory category, and only 1.32 % and 16.74% are in the excellent and very good categories, respectively. Conclusions. The current analysis concludes that there was a low positive relationship between reaction time and performance time of the finalist women sprinters only in sprint events of 100m and 100m hurdles during 2000 to 2020 Olympics, and the majority of the finalists belonged to the 'Average' category as per Gaval'a 5-point scale.